IMPACT OF IMPORT TARIFF POLICIES ON RICE DEMAND AND SUPPLY IN INDONESIA - pide, akhmad (Advances in Social Sciences Research Journal, 2020)
Indonesia’s economic policies cannot be separated to its rice policies since rice is the staple food for Indonesian people. The paper aims to find out the impact of rice import tariff policies on rice demand and supply in Indonesia. The research uses time series data in 1981-2018. Data obtained are analyzed using econometric model with simultaneous equation system. Estimation results show that rice supply was positively and significantly influenced by grain rice price in farmer level, amount of rice production, and rice supply of the previous year. Meantime, domestic rice demand was negatively and significantly influenced by domestic rice price and positively and significantly influenced by domestic rice demand of the previous year. The result of policy simulation indicates that scenario of policy combination through an increase in rice import tariff and government purchase price brings a sizeable impact on the increase in domestic rice production and rice demand and supply. Therefore, Indonesia needs to conduct protection to farmers in the form of rice import tariff imposition as well as government purchase price.